Prevalence of diabetic mellitus among obese and overweight people of 35 years and above in peri-urban area around Belgaum - Ashwini Narasannavar; Prakash Kumar Yadav; H.B. Rajshekhar (Al Ameen Medical College, 2017)
Background: Globally, the prevalence of diabetes is rising day by day. Diabetes is deeply rooted in Obesity and the other factor like aging of population. As per the WHO projection, diabetes is going to be the 7th leading cause of death in the year 2030. Objective: Estimate the Prevalence of diabetic mellitus among the obese and overweight people of 35 years and above. Materials and Methods: A Cross sectional study was conducted to estimate magnitude of diabetes among 335 obsese and overweight of age 35 years and above. Random blood glucose was estimated with cut off of >180mg/dl. Data was analyzed using SPSS version. Results: Out of 335 obese and overweight participants 19.4 percent were diabetic. 59.4 percent were females. Most of them (36.71%) were farmers, followed by 16 percent laborer. There was a significant association in between sex and the diabetic mellitus as the p-value was found to be less than 0.05. Conclusion: Prevalence of diabetes among obese has been increased. Hence, obesity is measured as the foremost risk factor for diabetes.